KONSEP PESERTA DIDIK KELAS VIII SMP YPK KOTARAJA JAYAPURA PADA POKOK BAHASAN GETARAN DAN GELOMBANG TAHUN AJARAN 2018/2019 - Parlin Parlin; Virman Virman; Paulus Lasmono Sugijo (Papua Journal of Physics Education, 2020)
The purpose of this study were: (1) to find out an increase in students' conceptual mastery in the experimental class applying the Contextual Teaching and Learning (CTL), (2) to find out the relationship between learning with CTL to students' conceptual mastery, and (3) to find out whether there is an influence of the application of CTL to students' conceptual mastery. This research uses quantitative data. The design of this study is one group pretest-posttest design. This research was conducted at the Kotaraja Jayapura YPK Middle School. The population in this study were all students of class VIII while the samples in this study were all students of class VIII C. Samples were 31 students. The results showed that: (1) there was an increase in every concept from the results of the N-Gain test score with 0.65 on the concept of vibration; 0.67 on the transverse wave concept, and 0.68 on the longitudinal wave concept; while the average N-gain score is 0.67 and is categorized on the medium category, (2) sig. 0.084> 0.05; then Ho is rejected and Ha is accepted; meaning that there is a very low relationship between variables X and Y, and (3) there is no influence between the variables X and Y with sig. values of 0.659> 0.05; then Ho is accepted and Ha is rejected so that there is no significant effect. Based on the results of these studies indicate that the learning approach CTL can improve students' conceptual mastery.Keywords: Contextual Teaching and Learning (CTL), Vibration, Waves.